Does Social Awareness Intervention Increase Pro-Environmental Behaviour? An Observational Study - Asha, Saiyeda Asea; Sultana, Most Aeysha (Social Science Review, 2023)
Pro-environmental behaviour is an indispensable feature for a habitable ecosphere. Thus, the discovery of the ways of enhancing pro-environmental behaviour is crucial. With this motive, the present study aimed to find out the impact of social awareness intervention (displaying cartoons and posters near the dustbin and cafeterias) on pro-environmental behaviour (here, throwing waste into a designated area/bin), where gender difference considered as an elementary factor. Data were gathered using observation (observation without intervention and observation with intervention) to get insight about how pro-environmental behaviour can be enhanced by social awareness. To generate more idea about the other influencing factors, semistructured interview was utilized. A total number of 644 cases were observed and 35 interviews were taken. The results depicted significant effect of social awareness on pro-environmental behaviour (Wald = 25.496, df= 1, p<.001) but no significant effect of gender on pro-environmental behaviour (p = .920). The findings are implementable to improve the pro-environmental behaviour among the Bangladeshi population with basic literacy. Future studies can be conducted using experimental design to gather more precise information about the ways of increasing pro-environmental behaviour. Social Science Review, Vol. 38(2), December 2021 Page 91-104